The Role of the Education Foundation for the Success of Private Schools in Jakarta - Doringin, Ferry (Bina Nusantara University, 2022)
The research discussed the role of education foundation in the success of Catholic schools in Jakarta. Based on the memories of the school's success and the current facts about school quality degradation as the background, the research asked about the importance of the foundation's role and its performance for school achievement. The research applied a qualitative approach and collected data using a deep interview method. Ten respondents were interviewed, including foundation (executive board), school leaders, and other education actors. The research used the respondents' answers to analyze the effectiveness of foundation management in running and leading the development of Catholic schools. The research concludes that foundation management is essential in guiding and leading schools to achieve their vision, mission, and objectives. The problem arises when the people in the foundation are chosen not because of their ability and function but because of other not significant reasons. Many education foundation personnel lack the knowledge of education principles and have no time to do their duties.